Balanced scorecard framework for IT project tender evaluation - Muhd Darus, Norida; Mohd, Haslina; Baharom, Fauziah; Mat Kasim, Maznah; Md Norwawi, Norita (2012)
Balanced scorecard (BSC),a strategic performance management tool, provides non -financial performance measures which reflect a more 'balanced' view of organizational performance. It has been extensively used in business industries, government agencies, and non-profit organizations worldwide particularly in aligning their business /management activities to the vision and strategy of their organizations.BSC can also improve internal and external communications, and monitor organizational performance against strategic goals.The BSC approach provides a clear prescription to organizations in identifying non-financial elements/components to be measured in order to 'balance' the financial perspective.The financial perspective is one of the key measures that are normally used in a tender evaluation process.The tender evaluation process is performed to determine and select suitable contractor for a particular project. Therefore, this paper aims to contribute an understanding on the effective use of the BSC and establish a conceptual framework for an information technology (IT) project tender evaluation. The framework describes the objectives and organizes the measures or criterions for tender evaluation based on four different perspectives: financial, internal business process, customer and learning, and growth perspectives.